Exploration of Self-Concept and Academic Achievement of Students After the Experience of Broken Home Families - Putri, Elga Diana; Nita, Rahma Wira; Triyono, Triyono; Asan, Mohammad Shafiq Bin (Program Studi Bimbingan dan Konseling Islam, 2025)
The rising divorce rate in Indonesia poses a significant challenge for students from broken homes, often negatively impacting their self-concept and academic achievement. Although some literature generalizes this impact as always negative, preliminary observations show that some individuals are able to excel despite these challenges. This study aims to explore in depth how students from broken homes perceive themselves and how this affects their academic achievement. This qualitative study uses a case study appzdroach with purposive sampling techniques to select three main informants, and data is collected through semi-structured in-depth interviews and non-participatory observation. The results show significant variations in the formation of self-concept; individuals with a positive self-concept see bitter experiences as motivation to achieve, while those with a negative self-concept tend to lose motivation. Thus, how individuals interpret their experiences is a key factor that determines resilience and academic success. This study contributes to a more nuanced understanding of psychological resilience in dealing with family trauma.